Deconstructing Two Roads: Applying the Psychology of Regret to Resolve the Mystery Surrounding Robert Frost’s Most Beloved Poem - Donald Thomas Carte (Humanities)
In the lifetime anthology of Robert Frost’s poetry, one poem consistently stands out as the most beloved and recognizable of his works. To the average reader, for over a hundred years “The Road Not Taken” has engendered images of individuality and the need to avoid following the crowd; this despite clear evidence within the verse that contradicts that reading. Most Frost scholars would agree the poem is the most misunderstood poem in Frost’s collection, and the academy has presented several intelligent and deeply introspective alternatives. However, none of these have garnered enough of a consensus to displace the initial misunderstanding. Through an interdisciplinary approach that makes use of the added epistemic approaches of historical research and the psychology of regret, this paper will uncover a hidden creation story for “The Road Not Taken”, and through a fulsome review of the poem’s origination, reveal a more basic axiom as to the purpose behind Frost’s two roads.